DESIGN OF MULTIFUNCTIONAL CYCLIC BENDING AND CYCLIC STRETCHABILITY TEST RIG FOR STRETCHABLE CONDUCTIVE INK - Manaf, M.Z.; Akop, M.Z.; Md. Fadzullah, S.H.S.; Ashikin, A.S.; Basori, B. (Journal of Advanced Manufacturing Technology (JAMT), 2020)
The reliability of flexible and stretchable printed circuit using conductive ink is important due to rapid growth of technology and demands of flexible and stretchable electronic products. The reliability assessment of the stretchable conductive ink (SCI) are important to ensure high functionality and durability over the designated operation lifetime. Thus, the development of cyclic bending test and cyclic stretchability test rig is required to investigate the functionality SCI under repeated loadings. The developed test rig has three main parts which are the movable end arm, adjustable fixed end arm and data gathering. The movable end arm is moving with help from stepper motor which controlled by power supply. Furthermore, the position of adjustable fixed end arm can also be adjusted according to the experiment percentage of stretchability. The test rig is attached with LCR meter to measure the resistivity of the printed circuit and the results are fully monitored by using computer. The development of multifunction reliability test rig for SCI in this project is able to offer a compact, simple and precise results based on the IPC 9204 test requirements.